2010
DOI: 10.19030/jber.v8i5.721
|View full text |Cite
|
Sign up to set email alerts
|

Determinants Of Risk Tolerance In The Baby Boomer Cohort

Abstract: Using data from 26,759 respondents, this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 5 publications
(11 reference statements)
1
21
2
Order By: Relevance
“…Several studies showed that there were a positive association between the levels of education and financial risk tolerance (Donkers, Melenberg and Van-Soest 2001;Chang, DeVaney and Chiremba, 2004;Kimball, Sahm and Shapiro, 2008;and Gilliam, Chatterjee and Zhu, 2010). Bellante and Green (2004) confirmed that the differences in education accounted for larger variations in asset allocation than any other determinants they investigated.…”
Section: Demographic Determinants Of Financial Risk Tolerancementioning
confidence: 75%
See 3 more Smart Citations
“…Several studies showed that there were a positive association between the levels of education and financial risk tolerance (Donkers, Melenberg and Van-Soest 2001;Chang, DeVaney and Chiremba, 2004;Kimball, Sahm and Shapiro, 2008;and Gilliam, Chatterjee and Zhu, 2010). Bellante and Green (2004) confirmed that the differences in education accounted for larger variations in asset allocation than any other determinants they investigated.…”
Section: Demographic Determinants Of Financial Risk Tolerancementioning
confidence: 75%
“…Grable and Lytton (1999) showed that a higher level of income has a positive effect on willingness to tolerate a risk. Similarly, Hartog, Ferrer-iCarbonell, and Jonker (2000); Faff, Hallahan and McKenzie (2009) and Gilliam, Chatterjee and Zhu (2010) confirmed that risk aversion fell as income or wealth increased. Hallahan, Faff and McKenzie (2004) also presented evidence that wealth and risk tolerance displayed a positive association.…”
Section: Demographic Determinants Of Financial Risk Tolerancementioning
confidence: 78%
See 2 more Smart Citations
“…An important implication of these studies is that men in general are more prone to risk-taking behaviour than women, and trade more excessively (Barber & Odean, 2001;Dwyer, Gilkeson, & List, 2002). Gilliam, Chatterjee and Zhu (2010) observed that gender differences in risk tolerance are consistent across generations and when controlling for other personal and household characteristics. A recent study by Faccio, Marchica and Mura (2016) shows that even the chief executive officer (C.E.O.…”
Section: Introductionmentioning
confidence: 93%